Cracks and Care: Pastoral-theological Reflections on the Gender Implications of the Covid-19 Pandemic - Kummer, Armin (Journal of pastoral theology, 2022)
This article explores the highly ambivalent impact the COVID-19 pandemic is having on gender identities, roles, and relations. Western media have reported widely on the regressive effects that have pushed women during the pandemic into the ‘double shift’ situation of having to combine home making with home office. What has caught less public attention are the many subtle ways in which the pandemic has subverted the traditional distinctions between public and private, ‘at home’ and ‘at work’, indoors and outdoors etc., that have long constituted the ideological foundation of gender relations in industrial societies. This article explores how the disruptive effects of the pandemic on the gender order provides opportunities for pastoral theology to support men in reworking their fractured male identities towards more life-giving visions of human flourishing.